Hair colouring: what a dermatologist should know? - George, Neethu Mary; Potlapati, Amruthavalli (International Journal of Research in Dermatology, 2021)
Hair is an important part of body and a major factor in self-image. A wide variety of hair cosmetic preparations are available and are used regularly by most of the world’s population. Hair colouring is one of the commonly done procedure. However, any chemical treatment, normal grooming habits and environmental exposure can produce changes in hair texture or hair breakage. It is necessary for a dermatologist to know the basis of hair colouring, the procedure and the possible side effects it can cause. Also post colour care is also to be known about to prevent further damage to treated hair. This article explains the basic chemistry and mechanism involved in hair dyeing and the basic facts a dermatologist should know.